Aberrant UBR4 expressions in Hirschsprung disease patients - Gunadi; Alvin Santoso Kalim; Estelita Liana; Aditya Rifqi Fauzi; Dian Nirmala Sirait; Dwiki Afandy; Sagita Mega Sekar Kencana; Eko Purnomo; Kristy Iskandar; Akhmad Makhmudi (BMC, 2019)
Abstract Background Recently, pathogenic alleles within ubiquitin N-recognin domain-containing E3 ligase 4 (UBR4) gene have been shown to be associated with Hirschsprung disease (HSCR). We determined the UBR4 expressions in Indonesian HSCR patients. Methods We analyzed the UBR4 expressions in the colons of HSCR patient and anorectal malformation (ARM) patient as control by real-time polymerase chain reaction (qPCR). Results Thirty-seven patients with non-syndromic HSCR and eighteen controls were involved in this study. qPCR revealed that the UBR4 expression was strongly decreased (0.77-fold) in the ganglionic group of patients with HSCR compared to the control group with ARM (ΔC T 2.43 ± 0.36 vs. 2.05 ± 0.69; p = 0.009), whereas the UBR4 expression was also significantly reduced (0.79-fold) in the aganglionic group of patients with HSCR compared to the control group with ARM (ΔC T 2.39 ± 0.46 vs. 2.05 ± 0.69; p = 0.044). However, the UBR4 expression change was not associated with gender (p = 0.35 and 0.80), nor with degree of aganglionosis both in ganglionic and aganglionic colons (p = 0.72 and 0.73), respectively. Conclusion Our study demonstrates that expression of UBR4 is decreased in both aganglionic and ganglionic colon of HSCR patients.